A decision model for determining public locations suitable for automated external defibrillator (aed) deployment: a case study in city of valencia - Ekmekci, Esin; Aragonés-Beltrán, Pablo; Rodríguez de Sanabria Gil, Rafael; Topcu, Ilker (Creative Decisions Foundation, 2017)
Automated external defibrillators (AED) offered a new perspective on resuscitation by enabling first-responders to deliver life-saving defibrillation within the critical first minutes after sudden cardiac arrest (SCA). This raised the question about where to place the AEDs. This study aims to provide a novel approach to the problem and to serve as a guideline for health policy decision makers in future projects. We used the Analytic Hierarchy Process (AHP) to form a decision model with four main criteria, and six sub-criteria. “Response time” was the most important criterion with an importance of 65.07%. Locations with the highest scores were a sports center, two stadiums, the central market, and the central bus station. A simple ranking of the alternatives would not be sufficient for the purpose of this study because the aim is to offer a guide for selecting locations for deploying AEDs rather than ranking the alternatives according to their suitability. Therefore, we formed priority groups. Sensitivity analysis showed that especially the alternatives in the first-priority group are not highly sensitive to changes, emphasizing their importance. https://doi.org/10.13033/ijahp.v9.i2.492
Keywords: Automated external defibrillator (AED); Organizacion de empresas; Public access defibrillation (PAD); Sudden cardiac arrest (SCA); Proyectos de ingenieria